Malay Pop: Mass Media Hegemony in Indonesia Popular Music - Kariko, Abdul Aziz Turhan (Lingua Cultura, 2009)
Article discusses the domination of Malay pop music through textual analysis of songs, observation of musical programs, and interviews with important figures. The research data were obtained by library research and analyzed through a critical theory approach to gain an understanding of the text and its effects. The article concludes that Malay pop contains a strong uniformity which may be termed a phenomenon in the context of the culture industry, while also being dominant because of its legitimacy created by the media. The nature of Malay pop is also very profitable for those participating in it, therefore the spirit of capitalism was also quite dominant in this context. There is also resistance from the indie music movement, and its attempts to fight regressive qualities of music that are legitimized in the mainstream mass media. Â